Processing‐Properties Correlation for a Rubber Toughened Wood Plastic Composite. Issue 1 (21st October 2022) - Mazzanti, Valentina; Malagutti, Lorenzo; Sbardella, Francesca; Mollica, Francesco
Abstract: Issues of environmental sustainability attract more and more attention to polymeric systems that can be considered environmentally friendly. A class of materials that meets the demand for a lower environmental impact are Wood Polymer Composites, or WPCs. These are thermoplastic polymers compounded with wood fibers or flour, usually coming from industrial or agricultural waste. With these materials, the greatest benefit is obtained by increasing the wood content, thus reducing the percentage of polymeric matrix. On the other hand, two of the main drawbacks coming from an increase in the wood content are brittleness and a significant reduction in processability. In this work, concentration will be on reducing brittleness by adding different amounts of a toughening agent (i.e., a thermoplastic elastomer) and on finding the optimal combination between processing conditions and elastomer content. This target will be obtained by comparing the tensile properties of all composites that are produced with different extrusion conditions with their apparent density.